Adding live, reactive telephone counselling to self-help literature does not increase smoking cessation. Issue 2 (1st May 2010) - Gilbert, Hazel
Abstract : Commentary on: Sood A Andoh J Verhulst S . "Real-world" effectiveness of reactive telephone counseling for smoking cessation: a randomized controlled trial . Chest 2009 ;136 :1229 –36 .